2014
DOI: 10.1038/ncomms5230
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog-expressing cells in the developing limb measure time by an intrinsic cell cycle clock

Abstract: How time is measured is an enduring issue in developmental biology. Classical models of somitogenesis and limb development implicated intrinsic cell cycle clocks, but their existence remains controversial. Here we show that an intrinsic cell cycle clock in polarizing region cells of the chick limb bud times the duration of Sonic hedgehog (Shh) expression, which encodes the morphogen specifying digit pattern across the antero-posterior axis (thumb to little finger). Timing by this clock starts when polarizing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 26 publications
2
65
0
1
Order By: Relevance
“…This is similar to what we found previously with the cells of the polarizing region (Chinnaiya et al, 2014). Thus, it is the developmental stage of the distal progenitors rather than the length of time for which they developed, that limits their ability to reset their cell cycle program in an early environment.…”
Section: Hh20 Wings With Hh27 Grafts Have a Normal Aersupporting
confidence: 76%
“…This is similar to what we found previously with the cells of the polarizing region (Chinnaiya et al, 2014). Thus, it is the developmental stage of the distal progenitors rather than the length of time for which they developed, that limits their ability to reset their cell cycle program in an early environment.…”
Section: Hh20 Wings With Hh27 Grafts Have a Normal Aersupporting
confidence: 76%
“…3C,D and ). This finding indicates that Shh signalling controls its own transcription in an auto-regulatory manner, possibly as part of an intrinsic timing mechanism (Chinnaiya et al, 2014). It was also evident that, by 24 h after cyclopamine treatment, wing buds were broader across the antero-posterior axis, so that by 96 h, the hand-plates of wings were increased in width by 1.2-fold (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…6A). G1-phase cells have been shown to deviate by <2% in limb buds of equivalently staged embryos incubated together (Chinnaiya et al, 2014). However, there was a considerable increase in the proliferative potential of polarizing region cells after 48 h (G1 cells, 56.5% vs 72.3% in control embryos) and 72 h (68.5% vs 80.6% ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, the involvement of Shh signaling in embryonic development of mammal species was discovered. Deprivation of certain molecules of this pathway was found to cause cerebellum atrophy and limb defects in rats (27)(28)(29)(30). Since neoplasms and embryonic development share similar molecular signaling processes, numerous studies have examined and demonstrated the core role of Shh signaling in maintaining tumor growth and cancer cell survival (12).…”
Section: Discussionmentioning
confidence: 99%